Kemampuan Membaca Nyaring Siswa Kelas II SD Negeri 11 Banda Aceh - masitrah masitrah; M. Husin; Suci Fitriani (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
Perusing out loud is an action for educators and understudies to get information, thoughts, and feelings of a writer and voice their writing orally with proper pronunciation and intonation. The ability to read aloud is one of the most important language skills, because it can enrich vocabulary, add information, and provide opportunities for students to listen and imagine. The plan of the issue in this study is "how is the ability to read aloud for second grade students of SD Negeri 11 Banda Aceh?". This study aims to describe the ability to read aloud second grade students of SD Negeri 11 Banda Aceh. The approach used in this research is a subjective methodology and a type of descriptive research. The subjects of this study were all 29 students of class II State Elementary School 11 Banda Aceh. Data collection techniques using observation and tests. The data analysis technique uses data reduction, and data presentation, as well as drawing conclusions and verification. The results of the study showed that the calculation of the average value was 76.55 and was in the sufficient category. The highest score obtained by students was 100 and the lowest score was 33. Judging from the formula, the percentage of students who scored very well (91-100) amounted to 9 people with a percentage (31.03%), and students who got good grades (83-90 ) amounted to 5 people with a percentage (17.24%). Meanwhile, students who got sufficient scores (75-82) were among 3 people with a percentage (10.34%). There were 12 students who got a low score (0-74) with a percentage (41.37%). The finish of this examination is the ability to read aloud second-grade students of SD Negeri 11 Banda Aceh is in the sufficient category. The author suggests teachers to be able to provide special guidance to students who have not been able to read aloud by increasing students' reading fluency and fostering self-confidence in students.